1999
DOI: 10.1117/12.356790
|View full text |Cite
|
Sign up to set email alerts
|

<title>Calf muscle blood flow and oxygen consumption measured with near-infrared spectroscopy during venous occlusion</title>

Abstract: We present non-invasive measurements of the calf muscle blood flow (BF) and oxygen consumption (OC) by near-infrared spectroscopy. We used a frequency domain tissue oximeter (modulation frequency: 1 10 MHz, wavelengths: 758 and 830 nm) to measure in real time (acquisition time: 0.64 s) the hemoglobin concentration and saturation. After 1-mm of baseline acquisition, we achieved venous occlusion by inflating a pneumatic cuff on the subject's thigh to a pressure of 60 mmHg. The cuffwas released after 1 mm. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…Baseline calibration values for these quantities are all comparable to the physiological norms found in other studies, 5,9,18,28,40,51 indicating fidelity of our instrumentation and methods for quantifying these parameters. For example, baseline BF values observed by NIRS and SGVP with the VO protocol in this study (0.88 AE 0.4 and 1.13 AE 0.6 ml∕100 ml∕ min) fell in the range of 0.7 to 4.0 ml∕100 ml tissue∕ min, reported in the literature.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Baseline calibration values for these quantities are all comparable to the physiological norms found in other studies, 5,9,18,28,40,51 indicating fidelity of our instrumentation and methods for quantifying these parameters. For example, baseline BF values observed by NIRS and SGVP with the VO protocol in this study (0.88 AE 0.4 and 1.13 AE 0.6 ml∕100 ml∕ min) fell in the range of 0.7 to 4.0 ml∕100 ml tissue∕ min, reported in the literature.…”
Section: Discussionsupporting
confidence: 61%
“…The overall sampling rate was ∼1 Hz to produce one data point for DCS and five data points for Imagent. Baseline absolute BF was obtained by fitting the slope of the THC increase measured by Imagent during VO, 18,28,35,40 while baseline absolute _ VO 2 was calculated by fitting the slope of the difference between [HbO 2 ] and [Hb] during the first minute of AO. 9,41 Following baseline calibrations, sampling for the hybrid DCS/Imagent was changed to a one-to-one with 1 Hz overall sampling rate for use in the exercise protocol: 600 ms for DCS correlation plus 300 ms for Imagent sampling.…”
Section: This Process Generates Absolute Values Of [Hbomentioning
confidence: 99%
See 1 more Smart Citation
“…Using NIRS, researchers have found that muscle oxygenation responses to exercise were associated with the severity of muscle vascular diseases. 19,[21][22][23][24][25][26][27] NIRS was also used to monitor gluteal tissue oxygenation index during bypass of bilateral hypogastric artery (HA) 3 and assess bypass graft patency in large vessels. 8,28 Skeletal muscle blood flow can be indirectly estimated by NIRS through applying venous occlusion to a limb at several discrete time-points.…”
Section: Near-infrared Spectroscopy (Nirs) For Measurement Of Tissue mentioning
confidence: 99%
“…8,28 Skeletal muscle blood flow can be indirectly estimated by NIRS through applying venous occlusion to a limb at several discrete time-points. 25 Unfortunately, the occlusion interrupts blood flow and makes it difficult for continuous measurement of blood flow during revascularization. A novel technology, the NIR diffuse correlation spectroscopy (DCS) flowmeter, was recently developed for noninvasive and direct measurement of relative change of blood flow (rBF) in deep tissues, [29][30][31][32][33][34][35][36][37][38][39][40] including skeletal muscles.…”
Section: Near-infrared Spectroscopy (Nirs) For Measurement Of Tissue mentioning
confidence: 99%